Some Good and Some Bad: Sand Fly Salivary Proteins in the Control of Leishmaniasis and in Autoimmunity - Aoki, Valeria; Abdeladhim, Maha; Li, Ning; Cecilio, Pedro; Prisayanh, Phillip; Diaz, Luis A.; Valenzuela, Jesus G. (Frontiers in Cellular and Infection Microbiology, 2022)
Sand flies are hematophagous insects responsible for the transmission of vector-borne diseases to humans. Prominent among these diseases is Leishmaniasis that affects the skin and mucous surfaces and organs such as liver and spleen. Importantly, the function of blood-sucking arthropods goes beyond merely transporting pathogens. The saliva of vectors of disease contains pharmacologically active components that facilitate blood feeding and often pathogen establishment. Transcriptomic and proteomic studies have enumerated the repertoire of sand fly salivary proteins and their potential use for the control of Leishmaniasis, either as biomarkers of vector exposure or as anti-Leishmania vaccines. However, a group of specific sand fly salivary proteins triggers formation of cross-reactive antibodies that bind the ectodomain of human desmoglein 1, a member of the epidermal desmosomal cadherins. These cross-reactive antibodies are associated with skin autoimmune blistering diseases, such as pemphigus, in certain immunogenetically predisposed individuals. In this review, we focus on two different aspects of sand fly salivary proteins in the context of human disease: The good, which refers to salivary proteins functioning as biomarkers of exposure or as anti-Leishmania vaccines, and the bad, which refers to salivary proteins as environmental triggers of autoimmune skin diseases.